Biological nitrogen fixation by rhizobium sp. native gliricidia (gliricidia sepium [jacq.] kunth ex walp.) under greenhouse conditions (2011)
An experiment was conducted under greenhouse conditions in order to evaluate the association and biological nitrogen fixation (BNF), six native strains of Rhizobium sp isolated from nodules gliricidia and a commercial strain (Rhizobiolc). Suspensions of 106 and 108 cells/mL for each of the strains studied and applied in two separate trials: the first with seeds and the second with seedlings 35 days of age gliricidia. In the seed test is calculated the cumulative percentage of germination for 7 days. In both trials after 42 days in seeds and seedlings 52 days in length was measured and stem diameter, leaf number, dry weight of aerial parts, number of nodules/plant and percentage of nitrogen. All treatments stimulated germination, growth and BNF, being better in the native strains at a concentration of 108 cells/mL, compared with the commercial strain and the control. These results indicate the positive effect exerted by Rhizobium sp., in promoting growth and BNF, which could be used for further studies to establish the production of a biofertilizer, allowing potentiate the production of crops by gliricidia for food arich cattle as source of protein in the Caribbean Biotechnology Center.